STUDENTS’ PERCEPTION OF LEARNING ENGLISH THROUGH BLENDED LEARNING - Aris TadiIa (Cahaya Ilmu Bangsa Institute, 2024)
Aris Tadila D0319021. Students' Perception in Learning English Through Blended Learning. Thesis majoring in English education, Teacher Training, and Education Faculty, Nahdlatul Ulama University Kalimantan Barat. This study aims: (1) to investigate how the blended learning process is, (2) to determine students’ perceptions of learning English through blended learning at class 8B Junior High in Darudda’wah Punggur. This study uses mixed methods so that researchers set observations, questionnaires, and also interviews as instruments to collect data in this study. Data were taken from class 8B which consisted of 26 students using a purposive sampling technique. The researcher analyzed the data using explanatory analysis. The results of this study indicate that the process of learning English through blended learning both offline (face-to-face) and online (WhatsApp application) in grade 8B students of Junior High School in Darudda’wah Punggur is well implemented. Students also show their positive and negative perceptions when learning English through blended learning. The researcher only suggests that in the future teachers should know more about the blended learning model so that the learning process becomes even better. Keywords: Students’ Perception, Blended Learning, Learning English